2011
DOI: 10.1113/jphysiol.2011.220434
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic BDNF signalling regulates long‐term potentiation at thalamo‐amygdala afferents

Abstract: Non-technical summary Long-term potentiation (LTP) in the lateral amygdala (LA) is a widely accepted cellular correlate of fear learning. In the present study we analysed the involvement of the neurotrophin brain-derived neurotrophic factor (BDNF) in amygdala LTP by stimulating selectively thalamic or cortical sensory inputs into the LA. In heterozygous BDNF knockout mice we observed that LTP in the cortico-amygdala pathway remained intact, whereas LTP in the thalamo-amygdala pathway was abolished. Likewise, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 56 publications
3
52
0
Order By: Relevance
“…After training, an IGF2 injection is capable of enhancing IA memory if injected into the hippocampus, but not the amygdala (Chen et al 2011), suggesting that although both the hippocampus and amygdala are important for IA memory, IGF2 is selectively recruited by the hippocampus in this task. BDNF is an important regulator of hippocampal plasticity and hippocampus-dependent memory, but can also modulate amygdala-dependent plasticity (Rattiner et al 2004(Rattiner et al , 2005Meis et al 2012). Indeed, BDNF signaling is required for LTP induced in thalamus -amygdala connections, but is not required for LTP induced at cortex -amygdala connections (Meis et al 2012), suggesting that BDNF may have varied, but restricted, roles in different brain regions.…”
Section: Spatial Regulation Of Gf Signaling During Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…After training, an IGF2 injection is capable of enhancing IA memory if injected into the hippocampus, but not the amygdala (Chen et al 2011), suggesting that although both the hippocampus and amygdala are important for IA memory, IGF2 is selectively recruited by the hippocampus in this task. BDNF is an important regulator of hippocampal plasticity and hippocampus-dependent memory, but can also modulate amygdala-dependent plasticity (Rattiner et al 2004(Rattiner et al , 2005Meis et al 2012). Indeed, BDNF signaling is required for LTP induced in thalamus -amygdala connections, but is not required for LTP induced at cortex -amygdala connections (Meis et al 2012), suggesting that BDNF may have varied, but restricted, roles in different brain regions.…”
Section: Spatial Regulation Of Gf Signaling During Plasticitymentioning
confidence: 99%
“…BDNF is an important regulator of hippocampal plasticity and hippocampus-dependent memory, but can also modulate amygdala-dependent plasticity (Rattiner et al 2004(Rattiner et al , 2005Meis et al 2012). Indeed, BDNF signaling is required for LTP induced in thalamus -amygdala connections, but is not required for LTP induced at cortex -amygdala connections (Meis et al 2012), suggesting that BDNF may have varied, but restricted, roles in different brain regions. Interestingly, in an object recognition task, BDNF release is increased following training and after 24-h testing in both the dentate gyrus and perirhinal cortex (Callaghan and Kelly 2012).…”
Section: Spatial Regulation Of Gf Signaling During Plasticitymentioning
confidence: 99%
“…The neurotrophin BDNF (brain-derived neurotrophic factor) is not only important for neuronal survival and differentiation in the developing brain, but it is also a crucial mediator for the induction and maintenance of synaptic plasticity (e.g., long-term potentiation), thereby modulating learning processes (see e.g., Lessmann et al 2003;Bekinschtein et al 2008;Gottmann et al 2009;Cowansage et al 2010;Yoshii and Constantine-Paton 2010;Meis et al 2012). It was demonstrated recently that BDNF signaling is also involved in cued fear learning.…”
mentioning
confidence: 99%
“…Recently, in heterozygous BDNF-knockout (BDNF+/−) mice it has been demonstrated that the reduced BDNF levels did not affect presynaptic glutamate release (Meis et al, 2012).…”
Section: Uncertainties or Inconsistenciesmentioning
confidence: 99%